2019
DOI: 10.1371/journal.pone.0211099
|View full text |Cite
|
Sign up to set email alerts
|

Social contexts as mediator of risk behaviors in Rwandan men who have sex with men (MSM): Implications for HIV and STI transmission

Abstract: IntroductionMen who have sex with men (MSM) are disproportionately impacted by HIV/AIDS resulting from risky sexual behaviors. Social and contextual factors are known to mediate risk behaviors, but there is limited information about the prevalence of risky sexual practices of Rwandan MSM and the concomitant socio-contextual determinants making it difficult to assess implications for preventing HIV/STI transmission in this key population.MethodsUsing exploratory qualitative design, we obtained socio-contextual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…The few studies performed among Rwandan MSM have shown evidence that this population is at particularly high risk of HIV infection and other sexually transmitted infections due to risky sexual behavior. 19 , 20 Ntale et al found the prevalence of HIV infection among Rwandan MSM to be 4.8%, 19 which is slightly higher than that among the general population, estimated at 3.0%. 21 Risky sexual behavior among Rwandan MSM includes high numbers of male and female sexual partners, providing commercial sex with both men and women, low condom use during anal and vaginal sex, and high mobility.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The few studies performed among Rwandan MSM have shown evidence that this population is at particularly high risk of HIV infection and other sexually transmitted infections due to risky sexual behavior. 19 , 20 Ntale et al found the prevalence of HIV infection among Rwandan MSM to be 4.8%, 19 which is slightly higher than that among the general population, estimated at 3.0%. 21 Risky sexual behavior among Rwandan MSM includes high numbers of male and female sexual partners, providing commercial sex with both men and women, low condom use during anal and vaginal sex, and high mobility.…”
Section: Introductionmentioning
confidence: 96%
“… 22 This is further complicated by intense societal stigma, social isolation, and discrimination, which play a significant role in individual susceptibility to engage in risky sexual behavior. 20 A recent study performed in Togo found the prevalence of HIV and anal hrHPV infections among MSM to be 26.1% and 44.9%, respectively, with anal hrHPV infection being higher among MSMLH than HIV-negative MSM, 23 indicating a high burden of HIV and anogenital HPV among this key population.…”
Section: Introductionmentioning
confidence: 97%
“…A 2015 study estimated an HIV prevalence among MSM (4.8%) higher than the national average (15). Furthermore, these studies described existence of bisexual partnerships among Rwandan MSM similar to settings around the world where same‐sex practices are stigmatized and sustained relationships are challenged (16‐18). However, whether MSM who have sex with both men and women in Rwanda have differential HIV and STIs risks remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…At the meso level, family, social network and community characteristics powerfully shape women's knowledge and behaviors about health, including cervical-cancer, as well as facilitate access to resources for support. The importance of social networks in influencing health-related knowledge and behaviors have been previously described (22,23,24). Studies have also documented ways in which social networks can be important sources of support for promoting health and wellbeing (25,26,27).…”
Section: Discussionmentioning
confidence: 97%